WORKLOAD AND NURSING STAFF SIZING IN INTENSIVE CARE UNITS - Mendes-Rodrigues, Clesnan; Costa, Karine Ellen Soares; Antunes, Arthur Velloso; Gomes, Fabíola Alves; Rezende, Geraldo Júnior; Silva, Durval Veloso (Journal of Health Care, 2017)
Although scores to calculate the workload in Nursing are common, they are not used regularly in Brazilian intensive care units (ICU) routine. In this context, the objective of this work was to evaluate the Nursing Activities Score (NAS) in four University Hospital's ICU, and verify the relation between System of Classification of Patients (SCP), proposed by Santos at al., in an Adult ICU and the effect on nursing sizing. The work was developed in a university hospital. All scores had asymmetric distribution and were concentrated in the first classes of distribution. The NAS was dependent on the shift of evaluating only for the two ICU Neonatal units, while there was no difference between the others. The Pediatric and Neonatal type III ICU had higher average scores and the Neonatal type II show the lower. Despite the differences between shifts to the scores of the NAS, the sizing was not dependent on the shift. The ASCP and the NAS led to a different scaling, the latter being higher, although they are correlated. The NAS has shown good applications to evaluated units and the patient classification system proved little effective in discriminating Adult ICU patients, mostly by low representation of minimum and intermediate care patients. The presence of differences between shifts may be related to greater knowledge of the patients by the morning team, reinforcing the need to understand the patient classification by different professionals or moments.
Keywords: Sizing; nursing; patient classification system; workload; nursing activities score